2021
DOI: 10.1002/celc.202001533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cobalt Doping on Enhanced Lithium Storage Performance of Nanosilicon

Abstract: High-capacity silicon anodes are attracting more attention, owing to their high theoretical capacities and low working potentials. However, massive volume changes and low intrinsic electric conductivity remain substantial challenges that limit the practical applications of these anodes in lithium-ion batteries (LIBs). In this study, cobalt-doped silicon nanoparticles with different Co concentrations (0.1 %, 0.3 %, and 0.5 %) are prepared by using a simple low-temperature annealing process and are studied as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
(110 reference statements)
2
10
0
Order By: Relevance
“…For Li1s spectra, the broad peak at 55.02 eV can be assigned to LiOH/ Li 2 CO 3 (∼ 55.0 eV), Li 2 O (∼ 55.6 eV), and LiCOR (54.5 eV), suggests that these are observed from the composition of SEI film. [45][46][47] Another convincing piece of evidence to support Mn 3 O 4 secondary phase formation is the measured CV scans for h-CoMO shown in Figure 6b; where all three scans show a shift of single cathodic peak to higher potentials from 0.25 to 0.3 V and two anodic peaks at 1.3 and 2.2 V, which is consistent with what was observed CV peaks for Mn 3 O 4 electrode in the literature. [49] Also, comparing the CV scans of MnO 2 (h-MO) to Mn 0.95 Co 0.05 O 2 (h-CoMO), the main cathode peak shifted from 0.27 to 0.3 V after 3 CV scans indicate Co doping progress in the oxidation of MnO 2 outer surface during cycling.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…For Li1s spectra, the broad peak at 55.02 eV can be assigned to LiOH/ Li 2 CO 3 (∼ 55.0 eV), Li 2 O (∼ 55.6 eV), and LiCOR (54.5 eV), suggests that these are observed from the composition of SEI film. [45][46][47] Another convincing piece of evidence to support Mn 3 O 4 secondary phase formation is the measured CV scans for h-CoMO shown in Figure 6b; where all three scans show a shift of single cathodic peak to higher potentials from 0.25 to 0.3 V and two anodic peaks at 1.3 and 2.2 V, which is consistent with what was observed CV peaks for Mn 3 O 4 electrode in the literature. [49] Also, comparing the CV scans of MnO 2 (h-MO) to Mn 0.95 Co 0.05 O 2 (h-CoMO), the main cathode peak shifted from 0.27 to 0.3 V after 3 CV scans indicate Co doping progress in the oxidation of MnO 2 outer surface during cycling.…”
Section: Resultssupporting
confidence: 88%
“…It is observed that the R ct value of h-CoMO is increased where the h-MO is decreased to a small extent, and it could be due to the morphological changes that occurred during Li + reactions with the anode materials. [46,23] The summarized R s , R SEI , and R ct values are shown in Table S3 The fast Li + reactions in the electrodes are estimated by the diffusion coefficient and can be determined by the following equation,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations